PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN CV. (XYZ) PEKANBARU - Iskandar, Iskandar; Yunasril, Ilma (Eko dan Bisnis: Riau Economic and Business Review, 2022)
Abstract : This research was conducted at CV. XYZ Pekanbaru, having its address at Jl. Cipta Karya â€“ Sialang munggu Village, Tampan District, Pekanbaru City. Riau Indonesia. The purpose of this study was to determine the effect of motivation on employee performance at CV. XYZ Pekanbaru. In addition, this study aims to complete the requirements for completing lectures at the Riau School of Economics (STIE-Riau). To achieve these objectives, research was conducted using a sample of 50 people, using the census method. The data analysis method used simple linear regression. Based on the test results obtained t-count is greater than t-table (10.128 > 2.011). It can be concluded that the motivation variable has a positive and significant effect on employee performance at CV. XYZ Pekanbaru. The value of R. Square (R2) of 0.681 (68.1%) explains that the motivation variable contributes to employee performance at CV. XYZ Pekanbaru is 68.1%. While the remaining 31.9% describes other independent variables that were not observed in this study. Recommendations that can be submitted are expected that the company pays attention to CV XYZ Pekanbaru to quickly adjust to the work environment because this gets the lowest response from respondents.Â